Clinical notion of the pathogenesis of tuberculosis generalization in HIV-infected patients - A. M. Panteleev (Туберкулез и болезни лёгких)
The follow-up study of the course of tuberculosis in 274 HIV-infected patients has established patterns in the development of its generalization with a consequential change of pulmonary, lymphogenous, and hematogenous stages. The periods of evolving generalization vary directly with the baseline level of CD4 lymphocytes when tuberculosis is detected. Generalized hematogenous tuberculosis develops with the lower level of CD4 lymphocytes and generalized lymphogenous tuberculosis does with their steady-state level. In the lymphogenous stage, Mycobacterium tuberculosis (MBT) spreads from the primarily involved intrathoracic lymph nodes along the lympathic routes to the nearest regional lymph nodes that are supraclavicular, subclavian, lateral cervical and axillary ones. MBT simultaneously penetrates along the lymphatic vessels accompanying the large vascular trunks into the lymph nodes of the retroperitoneal space and abdomen. Specific splenic involvement that may be a marker of the onset of a hematogenous MBT break is intermediate in the initial stages of hematogenous generalization.